Celiac Disease - Rampertab, S. Devi.; Mullin, Gerard E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2014)
Celiac Disease is an authoritative text intended to educate healthcare practitioners, gastroenterologists, physicians and nutritionists about the diverse manifestations, complications and management of gluten-sensitive enteropathy. The seventeen-chapter text provides the latest research on pathophysiology, including animal models, immunopathogenesis, genetics and the intestinal microflora. The book also features chapters on diagnosis, monitoring, complications and nutritional management, including therapies on the horizon. The text concludes with appendices that provide educational tools for symptom monitoring and dietary guidance. Written by specialists in their respective fields, Celiac Disease is a comprehensive resource that provides the healthcare practitioner an evidence-based practical guide to pathogenesis and therapy of celiac disease.      .
Introduction -- Definition of Celiac Disease and Gluten Sensitivity -- Epidemiology of Celiac Disease -- The Pathophysiology of Celiac Disease -- Immunogenetics of Celiac Disease -- Using Animal Models of Celiac Disease to  Understand the Role of MHC II -- Role of Gut Microbes in Celiac Disease Risk and Pathogenesis -- Presentation of Celiac Disease in Children and Adults -- Diagnosis of Celiac Disease -- Nutrition in Celiac Disease -- Dietary Supplements in Celiac Disease -- Monitoring and Follow-up of Patients with Celiac Disease -- Special Considerations in Children and Young Adults with Celiac Disease -- Novel and Experimental Therapies on the Horizon -- Morbidity and Mortality Associated with Celiac Disease -- Refractory Celiac Disease -- Celiac Disease: Dispelling Misconceptions and Myths -- Summary of Recommendations from the American College of Gastroenterology Celiac Disease Guidelines -- Resources for Celiac Disease Practitioners and Patients -- Taxonomic Relationships of the Major Cereal Grains -- Some Potential Sources of Hidden Gluten -- Key Elements in the Management of Celiac Disease -- Celiac Iceberg -- An Approach to Gluten Challenge for the Diagnosis or Exclusion of Celiac Disease -- An Approach to the Monitoring of Celiac Disease -- An Approach to the Diagnosis of Celiac Disease -- An Approach to the Patient with Non-Responsive Celiac Disease -- Dietary Reference Intakes (DRIs): Recommended Dietary Allowance and Adequate Intakes, Vitamins and Elements -- Dietary Reference Intakes (DRIs): Tolerable Upper Intake Levels, Vitamins and Elements.
Keywords: Gastroenterology .; Internal medicine; Primary care (Medicine).; Clinical nutrition; Gastroenterology; Internal Medicine; Primary Care Medicine; Clinical Nutrition